Antiphospholipid antibodies positivity as a potential risk factor for restenosis following arteriovenous fistula stenting in hemodialysis patients: a pilot study - Taghavi, Maxime; Lengelé, Adrien; Laureys, Marc; Jacobs, Lucas; Kaysi, Saleh; Collart, Frédéric; Demulder, Anne; Nortier, Joëlle (Frontiers in Medicine, 2025)
BackgroundThe arteriovenous fistula (AVF) is the preferred vascular access for hemodialysis. AVF stenosis is a common complication, often requiring balloon angioplasty. For recurrent stenosis, AVF stenting may be an option. Persistent antiphospholipid antibody (aPL) positivity is frequently observed in hemodialysis (HD) patients and is associated with AVF thrombosis and stenosis. This study aimed to evaluate AVF stent survival without stenosis in aPL-positive hemodialysis patients.MethodsA monocentric retrospective observational study was conducted on 35 patients who underwent AVF stenting between 1st January 2014 and 31st December 2023. The patients were divided into two groups: the aPL+ group [defined by a score of 3 or more based on the laboratory criteria of the 2023 ACR/EULAR for antiphospholipid syndrome (APS)] and the control group. Intrastent restenosis was defined as a chronic change in the AVFphysical examination or blood flow, confirmed by ultrasound (US) or angiography. Kaplan–Meier survival analysis was used to estimate the probability of stent survival without restenosis.ResultsThe prevalence of intrastent restenosis was significantly higher in the aPL+ group at 24 months. The Kaplan–Meier survival analysis showed a significantly lower probability of AVF stent survival without restenosis in the aPL+ group (age-adjusted Hazard Ratio, 2.13 [IC95%, 1.70–2.69]).ConclusionTo the best of our knowledge, we describe for the first time a statistically significant association between aPL+ and AVF intrastent restenosis. Intimal hyperplasia is a non-thrombotic lesion associated with aPL+ and is linked to the mammalian target of rapamycin (mTOR) signaling pathway. We hypothesize that aPL may contribute to intrastent restenosis by inducing intimal hyperplasia. Whether this phenomenon is mTOR-mediated and whether sirolimus-eluting stents or balloons could be a better option for aPL+ patients requires further study.